The formula for calculating the sum of all natural integers from 1 to n is well-known:
Sn = 1 + 2 + 3 + .... + n = (n2 + n)/2
Similary, we know about the formula for calculating the sum of the rst n squares:
Qn = 1 .1 + 2 . 2 + 3 .3 + ::: + n .n = n3/3 + n2/2 + n/6
Now, we reduce one of the two multipliers of each product by one to get the following sum:
Mn = 0 .1 + 1 . 2 + 2 . 3 + 3 . 4 + .....+ (n . 1) . n
Find an explicit formula for calculating the sum Mn.
Sn = 1+2+3+4+.......+n ="\\frac{( n\u00b2+n)}{2}"
Qn = 1.1 + 2.2 +3.3+......+n.n = "\\frac{n\u00b3}{3}+\\frac{n\u00b2}{2}+\\frac{n}{6}"
So Qn - Sn ="[\\frac{n\u00b3}{3}+\\frac{n\u00b2}{2}+\\frac{n}{6}]-\\frac{( n\u00b2+n)}{2}"
=> {1.1 + 2.2 +3.3+......+n.n } - {1+2+3+.......+n} = "\\frac{n\u00b3}{3}+\\frac{n\u00b2}{2}+\\frac{n}{6}-\\frac{n\u00b2}{2}-\\frac{n}{2}"
Rearranging the left hand side
(1.1-1)+(2.2-2)+(3.3-3)+....+(n.n-n) = "\\frac{n\u00b3}{3}-\\frac{n}{3}"
=> 1(1-1)+2(2-1)+3(3-1)+.....+n(n-1) = "\\frac{n\u00b3}{3}-\\frac{n}{3}"
=> 1.0+2.1+3.2+4.3+....+n(n-1) = "\\frac{n(n\u00b2-1)}{3}"
=> 0.1+1.2+2.3+3.4+....+(n-1).n = "\\frac{n(n\u00b2-1)}{3}"
So Mn = "\\frac{n(n\u00b2-1)}{3}"
Comments
Leave a comment